2006
DOI: 10.1128/aac.50.1.148-155.2006
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Activity of Moxifloxacin against 923 Anaerobes Isolated from Human Intra-Abdominal Infections

Abstract: The in vitro activity of moxifloxacin against 923 recent anaerobic isolates obtained from pretreatment cultures in patients with complicated intra-abdominal infections was studied using the CLSI M11-A-6 agar dilution method. Moxifloxacin was active against 87% (96 of 110) Bacteroides fragilis strains at <1 g/ml and 87% (79 of 90) B. thetaiotaomicron strains at <2 g/ml. Species variation was seen, with B. uniformis, B. vulgatus, Clostridium clostridioforme, and C. symbiosum being least susceptible and accountin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
37
1
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 67 publications
(40 citation statements)
references
References 24 publications
0
37
1
2
Order By: Relevance
“…The most recent national survey (27) reported that 27% of B. fragilis, 26% of B. thetaiotaomicron, 38% of B. ovatus, and 55% of B. vulgatus isolates were resistant to moxifloxacin. A study of strains isolated from intra-abdominal infections (2001 to 2004) found 87% of B. fragilis and 87% of B. thetaiotaomicron isolates to be susceptible to moxifloxacin (143). The overall results showed that 86% (303/363) of all B. fragilis group isolates and 417/450 isolates of all other anaerobic genera and species, including Fusobacterium, Prevotella, Porphyromonas, C. perfringens, Eubacterium, and Peptostreptococcus spp., were susceptible to Յ2 g/ml of moxifloxacin.…”
Section: Fluoroquinolonesmentioning
confidence: 89%
See 1 more Smart Citation
“…The most recent national survey (27) reported that 27% of B. fragilis, 26% of B. thetaiotaomicron, 38% of B. ovatus, and 55% of B. vulgatus isolates were resistant to moxifloxacin. A study of strains isolated from intra-abdominal infections (2001 to 2004) found 87% of B. fragilis and 87% of B. thetaiotaomicron isolates to be susceptible to moxifloxacin (143). The overall results showed that 86% (303/363) of all B. fragilis group isolates and 417/450 isolates of all other anaerobic genera and species, including Fusobacterium, Prevotella, Porphyromonas, C. perfringens, Eubacterium, and Peptostreptococcus spp., were susceptible to Յ2 g/ml of moxifloxacin.…”
Section: Fluoroquinolonesmentioning
confidence: 89%
“…Moxifloxacin has been studied and approved by the FDA as monotherapy in intra-abdominal infections in adults (76,90) and has shown activity against intra-abdominal anaerobic isolates (143,144). However, concern over increasing fluoroquinolone resistance in both E. coli and B. fragilis group species has made clinicians cautious in its use in intra-abdominal infections (76).…”
Section: Fluoroquinolonesmentioning
confidence: 99%
“…Many clinical laboratories do not identify anaerobes, especially to the species level (12). However, identifying some of the clinically common clostridial isolates is necessary because susceptibility is often species specific, and the importance of performing susceptibility testing on clostridial isolates other than C. perfringens has been shown in several studies (10,11,36). Our susceptibility results were different from those of the study by Finegold et al (9) in that most strains in all five species appeared resistant to moxifloxacin by use of FDAdefined breakpoints.…”
Section: Resultsmentioning
confidence: 99%
“…Its potent antianaerobic activity seems to be close to that of sitafloxacin and comparable to that of trovafloxacin (1,3,8,11,15,20,21,25,26). Fujikawa et al comprehensively studied the antibacterial activities of DX-619 and reference agents, including IPM and LVX (5).…”
mentioning
confidence: 99%
“…Newer quinolones, such as sparfloxacin and levofloxacin (LVX), have improved in vitro activities against anaerobic bacteria but still have limited activities against certain gram-positive and gram-negative anaerobic bacilli (3,7,8,11,12,15,23,25). Some of the newer fluoroquinolones are much more active to both gram-positive and gram-negative anaerobic bacteria (3,8,11,12,15,20,26). DX-619 is a new derivative of quinolone, defined as a des-F (6) quinolone that lacks the six-position fluorine characteristic of the previous generation of fluoroquinolones.…”
mentioning
confidence: 99%